Heat shock protein–peptide complex in the treatment of glioblastoma. (June 2011) - See, Alfred P; Pradilla, Gustavo; Yang, Isaac; Han, Seunggu; Parsa, Andrew T; Lim, Michael
Vaccination immunotherapies offer the promise of long-term tumor control, and preclinical trials have found promising results. Active immunotherapy uses the adaptive immune response to specifically kill tumor cells. Tumor-specific antigens are processed by antigen-presenting cells and recognized by specific effector lymphocytes. However, basic vaccination strategies with tumor lysates have been unsuccessful in inducing antiglioma immunity in clinical trials. Gliomas are known to modulate the activity of antigen-presenting cells to reduce antitumor immune activity. Recently, tumor-derived heat shock proteins have been found to more effectively activate the immune response. Widely expressed, heat shock proteins are thought to present protein peptide fragments in a format conducive to processing by antigen-presenting cells. As a part of the protein synthesis machinery, peptides complexed with heat shock proteins are effectively representative of antigens expressed by the cell; these peptides convey the specificity of this vaccination strategy. The heat shock protein–peptide vaccine is one of many promising immunotherapeutic strategies being evaluated in clinical trials. These can be broadly classified as active, passive and adoptive, each with advantages and disadvantages. Here, we compare and contrast heat shock protein–peptide vaccines with other immunotherapies and describe the outcomes of clinical trials to date.